Cryptocurrencies and the future of money. Going beyond the hype: how can digital currencies serve society? - Seiferling, Mike; Ahmed, Thamin; ElBahrawy, Abeer Yehia; Chan, Keith; Padilha, Tales (IE University, 2020)
Since their inception in 2008 and the subsequent enthusiasm, media attention, delusion, reflection, and continuous innovation, ‘cryptocurrencies’ have become one of the most interesting and perhaps most misunderstood phenomena of the early 21st century. Their popularity and potential for ‘disrupting’ and improving traditional financial systems, however, have led to an expanding list of media commentaries, research papers, and policy reports. Unfortunately, many of these contributions have tended to focus on the contemporary positivist side of cryptocurrency without considering the normative intentions of its creators or, perhaps more importantly, the historical context under which money and monetary systems have evolved. These contributions have also tended to focus on digital money from a single disciplinary viewpoint (computer science, economics, finance) without a great deal of consideration or integration of the valuable inputs from other perspectives. The idea of money has evolved continously over time. In the context of the technological innovations of the 21st century, it has become a phenomenon with a wider range of feasible possibilities, some of which were in fact proposed as far back as the early 20th century. To give some idea of the new range of types of money, the Bank for International Settlements (BIS) published a series of taxonomies including the ‘money flower’ and more general taxonomies that distinguish between central bank-issued currencies (which are a liability on the central bank balance sheet) and private-sector issued digital currencies (which are not the liability of anyone). Within this wider context, there exists a variety of types of money, each of which has different underlying characteristics, or attributes. Introduction/ Preface widely accessibleComplete report
Keywords: Cryptocurrency; Criptomonedas; Policies; Políticas; Perspectives; Perspectivas; Disrupting economy; Economía disruptiva